Pengurangan Pencemaran Lingkungan Dengan Pembuatan Tempat Sampah Bakar Untuk Menciptakan Lingkungan Bersih Dengan Pendekatan PAR Di Desa Supiturang Kabupaten Lumajang - Fauzi, Ahmad; Bilqis, Aulia Malikal; Sholikhah, Rif'atus; Aini, Nur Rohmatul; Fadhilah, Syafira Nur; Farera, Jihan; Nurwahidah, Erninda Arianti; Margaretha, Cindy; Ali, Ismil Yanuar (PUDAK: Local Wisdom Community Journal, 2023)
During group 71 KKN (Real Work Lecture) activities in Supiturang Village, Lumajang Regency. One of the projects carried out is the construction of burning trash cans. Previously, local people still threw away and burned rubbish carelessly, which had an impact on the environment, both air and land. The target is to make the village environment cleaner and more orderly, as well as reducing the amount of rubbish strewn on roads and open land. This research uses the Participatory Action Research (PAR) method which aims to achieve positive results. The research findings show that providing burnt bins to improve environmental quality is very effective. sharpen the sensitivity, concern and skills of the community in protecting the environment so as to create a clean and healthy environment.